2021
DOI: 10.1177/02692155211040930
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of the enfranchisement scale of the community participation indicators

Abstract: Objective: This study examined the construct validity of the Enfranchisement scale of the Community Participation Indicators. Design: We conducted a secondary analysis of data collected in a cross-sectional study of rehabilitation outcomes. Subjects: The parent study included 604 community-dwelling adults with chronic traumatic brain injury, stroke, or spinal cord injury. The sample had a mean age of 64.1 years, was two-thirds male, and included a high proportion of racial minorities ( n = 250, 41.4%). Main me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…It is possible that these differences may be attributed to the experience of enfranchisement across diagnostic groups and their associated clinical presentations (eg, differences in age, physical function, communication, and social skills). However, previous studies have shown that there are few differences in enfranchisement scores across diagnostic groups (TBI, stroke, spinal cord injury) in samples larger than ours 5,6,7,36 . It is also possible that our results differed because of differences in sampling approaches.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It is possible that these differences may be attributed to the experience of enfranchisement across diagnostic groups and their associated clinical presentations (eg, differences in age, physical function, communication, and social skills). However, previous studies have shown that there are few differences in enfranchisement scores across diagnostic groups (TBI, stroke, spinal cord injury) in samples larger than ours 5,6,7,36 . It is also possible that our results differed because of differences in sampling approaches.…”
Section: Discussionmentioning
confidence: 62%
“…However, previous studies have shown that there are few differences in enfranchisement scores across F I G U R E 2 Distribution of change scores: Importance subscale diagnostic groups (TBI, stroke, spinal cord injury) in samples larger than ours. 5,6,7,36 It is also possible that our results differed because of differences in sampling approaches. We specifically recruited people with recent brain injuries, or who were still undergoing rehabilitation therapies, whereas previous studies have intentionally sought participants in a more chronic or stable phase of recovery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2011, a two-day evaluation of 100 professional American football players and 50 non-confrontational athletes was conducted in the United States, which included: sports history, history of previous brain injury; cognitive, emotional and behavioral testing; lumbar puncture for cerebrospinal fluid protein levels; EEG and neuroimaging, using DTI, fMRI, MRS and other technical means [8]. Another recent clinical prospective study of brain injury in athletes was conducted by American neuroscientists.…”
Section: Follow-up Study Of Casesmentioning
confidence: 99%
“…Convergent and discriminant validity are established to evaluate construct validity (Kersey et al 2022). Convergent validity occurs when measured items converge on the underlying construct; AVE > 0.50 indicates convergent statistical validity (Hair et al 2021).…”
Section: Measurement Assessment Model-outer Modelmentioning
confidence: 99%